Growth and root yield of carrot as affected by magnetic water and sowing times - Kanimarani, Sawsan M.S. Ali; abdulrahman, Maqsood K.; Danha, Hawraz P. (Sulaimani Journal for Pure and Applied Sciences, 2016)
This study examines effects of two sowing times (28/10 and 14/11 of 2014) and different levels of magnetic treatment of irrigation (0, 2500, 5000gauss) on productivity and yield of carrot plants. A pot experiment was conducted at the Agriculture Research Center, Ministry of Agriculture in Kurdistan region-Iraq. This study was carried out during 28-10- 2014 and 14-5-2015 the two factor experiment was laid out in complete randomized design with four replicates, each replicate contain three plants. Data were collected from all plants at harvest time and statistically analyzed. Comparisons between means were made by using least significant differences test (LSD) at 5% probability. Magnetized water at the level of 2500gause caused the most significant effects on plant length (55.58cm), root length (30.19cm), (root diameter (35.14mm) and root dry weight (128.19gm). However, the sowing time 14/11 was more effective on plant length (54.64cm) and vegetative growth fresh weight (17.64gm). While the longest root obtained when the seeds sown in 28/10. On the other hand the interaction of 2500gauss and 4/11/2014 sowing time gave the maximum plant length, shoot fresh weight and root diameter (59.67cm, 20.63 gm and 43.75mm respectively), but the longest root and highest root fresh weight were found in the interaction of the same level of magnetic water with 28/10/2014 sowing time. The highest amount of the chlorophyll in the leaves (52.815%) was measured from the interaction of 2500gauss magnetic water and 14/11/2014 sowing time, and the best carotene content in the roots (3.427mg/ml) was obtained from 5000gauss magnetic water in the same sowing time.
Keywords: Carrot; growth; yield,magnetic water,sowing time